USING NUMBERED HEADS TOGETHER TO IMPROVE STUDENTS’ VOCABULARY LEARNING OUTCOMES: A Classroom Action Research with The Students of SMP Islam Al - Hadi Sukoharjo - Cahyati Praba Hardini; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
This research is conducted to fulfill the following aims: 1) to describe a cooperative learning method namely Numbered Heads Together, 2) the effectiveness of Numbered Heads Together to improve student learning outcomes in the seventh grade students of SMP Islam Al - Hadi Sukoharjo in 2020/2021 Academic Year. This research was conducted by applying Collaborative Action Research. The procedure of this research was conducted in two cycles. Each cycle consists of two sessions. The procedure of action research is conducted in 4 steps namely planning, action, observation and reflection. There are two kinds of data namely non test, which consists of observation, interview, documentation and photograph; and test which conducted by giving a pre-test before the research begins and post-test at the conclusion of the research. The quantitative data was analyzed by using SPSS 23 Statistic Software to calculate the nonindependent t-test. The qualitative data analysis consists of three concurrent flows of activity: data reduction, data display, and conclusion drawing and verification. The research shows the improvement of mean score from pre-test which is 57.41, to 67.05 on post-test 1 and finally 76.82 on post-test 2. Therefore, it can be concluded that: 1) Numbered Heads Together as a cooperative learning model is a learning strategy which emphasized student’s individual accountability, 2) Numbered Heads Together is effective in improving student learning outcomes in vocabulary.   Key words: Numbered Heads Together, Vocabulary Mastery, Classroom Action Research.